Paradise Peak precious metals mill begins production ahead of schedule and under budget - L. J. Buter; D. J. Collins (Society for Mining, Metallurgy & Exploration, 1986)
Introduction FMC's Paradise Peak gold mine was discovered by staff geologists in July 1983. Located south of Gabbs, in western Nevada, the deposit contains about 11 Mt (12 million st) of ore grading at 3.6 g/t (0.105 oz per st) of gold and 129 g/t (3.75 oz per st) silver. It is estimated that the ore contains 34 t (1.1 million oz) of recoverable gold and 933 t (30 million oz) of recoverable silver. The 3.6 kt/d (4000 stpd) mill began operation April 14, 1986, just 18 months after Davy McKee completed a feasibility study and construction, and two-and-a-months ahead of schedule. It also came in about 10% under budget at a cost of about $100 million. Crushing Run-of-mine ore is delivered from the mine in 45-t (50-st) haul trucks to a 272-kt (300,000-st) capacity open air stockpile. Ore is reclaimed using 5 m3 (7 cu yd) front-end loaders that feed a 91-t (100-st) hopper equipped with a 610- x 610-mm (24- x 24-in.) grizzly. A 1.4- x 11-m (54-in. x 35-ft) apron feeder delivers ore from the hopper by way of a vibrating grizzly screen with 127 mm (5 in.) openings to a 1- x 1.3-m (43- x 51-in.) Rexnord jaw crusher. Crushed material is conveyed to a 1.8- x 4-m (6- x 14-ft) Link Belt vibrating screen equipped with a 50-mm (2-in.) manganese grizzly bar deck. Screen oversize is fed to a 1.7/0.6-m (5.5 ft) Rexnord standard cone crusher. Product from this crusher joins the -50 mm (-2 in.) screen undersize and is conveyed to a 136-t (150-st) surge bin. Three hydraulically driven belt feeders deliver ore from the ore bin to three 2 x 6 m (7 x 20 ft) Link Belt single-deck tertiary screens fitted with 6 x 25 mm (0.25 x 1 in.) slotted polyethylene screens. Screen undersize - -6 mm (-0.25 in.) rock - is conveyed to a 3.6-kt (4000-st) ore storage bin. Screen oversize is delivered by way of a conveyor to a 91-t (100-st) surge bin. From this bin, two belt feeders feed ore to two 1.7 m (66 in.) Rexnord Gyradisc crushers, which are in closed circuit with the tertiary screens. Design features include magnetic protection for tramp iron removal and sloping floors and pump sumps for ease of clean up. Dust scrubbers keep the working environment clean and in compliance with state dust emission regulations. Grinding Two 1 x 4.5 m (3.5 x 15 ft) belt feeders deliver ore from the fine ore bin to a conveyor belt that feeds it to the 5 x 7 m (16 x 22 ft) Allis-Chalmers ball mill. The conveyor belt is equipped with a Merrick weightometer. This controls feed rate to the ball mill by speed control on the hydraulic motors driving the feeders. The 2.6 MW (3500 hp) powered mill grinds 3.6 kt/a (4000 stpd) to an average grind of 85% -75 µm (-200 mesh). The mill is in closed circuit with four 660 mm (26 in.) Krebs cyclones. Three of these are normally in operation while one is a standby. Warman pumps feed the cyclones through a cyclone distribution manifold. The cyclone underflow returns to the ball mill, which has a 300% average circulating load. Mill discharge pH is 11, and that is obtained through pebble lime addition to the feed belt. Cyclone overflow is sampled using a Heath & Sherwood two-stage sampler. It then flows to a 27-m-diam (90-ft-diam) Eimco thickener. Thickener overflow is returned to the grinding circuit, while underflow at 50% solids is pumped to the leaching circuit. Grinding-circuit design features include a steeply sloped floor for ease of clean up, an open area over the pumps for maintenance accessibility, and a ball hopper with a self discharge bottom to speed ball addition. Other features include a mill liner handler and an air clutch that connects the mill motor to the mill.